ANALISIS FAKTOR DEMOGRAFI, KOMPENSASI, KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KOMITMEN ORGANISASI (Studi Pada Perusahaan Manufaktur Sektor Logam) - Octavia, Lydia (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine the effect of demographics and compensation on job satisfaction mediated by job satisfaction. The research sample was selected using the saturated sample method in which all employees at the Metal Sector Manufacturing Company, totaling 109 employees, were used as samples. This research is a quantitative research with causality analysis approach. The data were analyzed using the SEM-PLS method with the help of SmartPLS 3 software. The results showed that demographic factors had a negative effect on organizational commitment and compensation, but had no significant effect on job satisfaction. Compensation has a positive and significant effect on job satisfaction and organizational commitment, and job satisfaction also has a positive and significant effect on organizational commitment. Compensation can mediate the relationship of demographic factors to organizational commitment and job satisfaction. Job satisfaction can mediate the relationship of compensation to organizational commitment, but cannot mediate the relationship of demographic factors to organizational commitment.